QT Interval Dispersion as a Predictor of Clinical Outcome in Acute Ischemic Stroke - Tang, Hefei; Sun, Jiayao; Wang, Yu; Jie, Xu; Ma, Yan; Wang, Anxin; Zhang, Yijun; Wang, Xingao; Wang, Yongjun (Frontiers in Neurology, 2021)
Background and Purpose: QT dispersion (QTd) abnormalities are widely documented in stroke patients. However, their associations with functional recovery and recurrent vascular events after acute ischemic stroke (IS) have not been thoroughly investigated. Methods: IS patients registered in the Blood Pressure and Clinical Outcome in transient ischemic attack (TIA) or IS (BOSS) registry between 2012 and 2014 within 24 h of onset were analyzed. In this prospective observational study, we identified 1522 IS cases with adequate electrocardiographic evaluations to assess QTd after the index stroke. Patients were divided into four groups according to the quartile of QTd, with the lowest group as the reference. Recurrent vascular events and functional recovery were prospectively collected at 1-year follow-ups. Multiple logistic regressions and Cox proportional hazards models were utilized to investigate the association between QTd and outcome events. Results: The mean QTd across all cases was 57 milliseconds (40-83). Functional dependency or death was documented in 214 (14.98%) cases at 1 year. After adjusting for age, sex, medical history, admission NHISS score, and other covariates, the prevalence of functional dependency or death showed significant differences according to the magnitude of QTd. Compared with patients in the first quartile, patients in the fourth quartile had significantly higher risks for functional dependence or death (mRS score 3–6) at 1 year (adjusted odds ratio [95% confidence interval]: 1.619 [1.019–2.572]). However, there were no significant differences in the event outcomes at 1 year after the index stroke. Conclusions: QTd was associated with poor functional outcomes at 1 year. QTd is a useful surrogate marker for adverse functional prognosis, which might help to stratify risk in patients with acute IS.